The Effect Of Perineal Massage On The Insidence Perineal Rupture In Labour In Nene Mallomo Hospital Sidenreng Rappang - Jamir, A. Fatimah; Tajuddin, Titin (Bunda Edu-Midwifery Journal (BEMJ), 2021)
Background: one of the causes of direct maternal death related to childbirth is bleeding (28%). Perineal rupture is the most common cause of post partum hemorrhage after uterine atony. One way to reduce perineal rupture is to do perineal massage to train and stretch the perineal tissue to make it more soft and elastic. Objective: to determine the effect of perineal massage on the incidence of perineal rupture in labor. Methods: This study was a quasi-experimental design with an "Equivalent control group design" approach. The population in this study were all trimester III primigrvida pregnant women at Nene Mallomo Hospital, Sidenreng Rappang Regency. Sampling using purposive sampling technique, as many as 20 people were divided into two groups, namely 10 people in the intervention group and 10 people in the control group. Data collection using SOP, observation sheet and partograph then the data is processed and analyzed using computer (SPSS) version 20. Data analysis includes univariate analysis by looking for frequency distribution, bivariate analysis with Wilcoxon test with significance level α (0.05). Results: based on the results of statistical tests using Willcoxon, the results obtained p = 0.027 kurang dari α= 0.05, so Ho was rejected, which means that there was an effect of perineal massage on the incidence of perineal rupture in childbirth at the Nene Mallomo Hospital, Sidenreng Rappang Regency. The intervention group experienced less rupture of 4 people (20%) compared to the control group of 7 people (35%). Conclusion: There is an effect of perineal massage on the incidence of perineal rupture in labor.